Nicaragua : Staff Report for the 2001 Article IV Consultation and the Staff-Monitored Program (SMP) for July-December 2001. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Nicaragua showed weak economic performance owing to trade shocks, a decline in investment, and slippages in the fiscal and monetary areas, under the Poverty Reduction and Growth Facility Arrangement. Executive Directors noted that an effective implementation of the fiscal program under the Staff Monitored Program (SMP), together with the envisaged privatization and structural reforms, is crucial for maintaining macroeconomic stability. They welcomed the steps to deepen trade liberalization, improve liquidity management, and strengthen the banking system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet